Makna Tahapan Adat Perkawinan Belis Gading Gajah Suku Lamaholot di Adonara Nusa Tenggara Timur - Doni, Maria Bulu; Bae’ah; Rosada, Amrina; Astuti, Reni; Kuncoro, Muhammad Bagus Anjas (Jurnal Ilmu Sosial dan Budaya Indonesia, 2025)
This article discusses the meaning and stages of the belis gading gajah (elephant tusk dowry) marriage tradition as an essential part of the cultural heritage of the Lamaholot ethnic group in Adonara, East Nusa Tenggara. The belis tradition is not merely a customary requirement for marriage but also carries deep philosophical, social, and symbolic values. The elephant tusk belis symbolizes respect for women, male responsibility, and the strengthening of inter-family relationships. Using a descriptive-qualitative approach based on literature review, this article explores the process and significance of belis from the Lamaholot cultural perspective ranging from family deliberations, the payment of mother’s milk money, Opu Lake, to the formal handover of the elephant tusk belis. The study reveals that this tradition serves not only as part of a wedding ritual but also as a means of preserving noble values, cultural identity, and the kinship system of the Lamaholot community, which continues to be upheld today.